Mos geometricus v. Reality - Jürg Gassmann; Samuel Gassmann (Bern Open Publishing, 2019)
The non-lethal simulated training of lethal reality, whether it be single combat or war, was historically a question of life and death. We provide an analytical framework for evaluating historical precedents in fight simulations by focussing on two key questions: What was the philosophy guiding the conception of reality - in particular, did historical practitioners see reality as deterministic, and if not, how did they see it? And how did the simulations deal with the elements of quantity, quality, timing, and information? The analysis shows that our ancestors' perception of the reality of fighting chan-ged over time, as their interpretations of reality for the world at large changed. Considerable intellectual effort and ingenuity were invested into attempts to understand reality and formulate corresponding realistic simulations, making these ludic artefacts reflective, sometimes iconic for, and occasionally ahead of their historical-cultural context. Seemingly irrational phenomena, such as the persistence of lethal duelling, had perfectly pragmatic elements.